Analysis of "Bondhu Garage Project" and "Clarke Energy Inauguration Project": contrast between theories and pragmatic application - Haque, Md. Ashraful (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015